2013
DOI: 10.1007/s00382-013-1744-6
|View full text |Cite
|
Sign up to set email alerts
|

Added value of convection permitting seasonal simulations

Abstract: In this study the added value of a ensemble of convection permitting climate simulations (CPCSs) compared to coarser gridded simulations is investigated. The ensemble consists of three non hydrostatic regional climate models providing five simulations with *10 and *3 km (CPCS) horizontal grid spacing each. The simulated temperature, precipitation, relative humidity, and global radiation fields are evaluated within two seasons (JJA 2007 and DJF 2007-2008 in the eastern part of the European Alps. Spatial variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
268
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(288 citation statements)
references
References 40 publications
18
268
0
2
Order By: Relevance
“…Results with convection-permitting simulations indicate improved spatio-temporal characteristics of heavy hourly events (Ban et al 2014;Chan et al 2014b), and a better scaling with temperature (Ban et al 2014). Further, the convection-permitting approach improves the simulation of the diurnal cycle of summer precipitation (Hohenegger et al 2008;Prein et al 2013). Tölle et al (2014) demonstrated that the influence of land use/cover change is more pronounced when considering the convection-permitting scale, suggesting that local effects of land management are more important than previously thought.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Results with convection-permitting simulations indicate improved spatio-temporal characteristics of heavy hourly events (Ban et al 2014;Chan et al 2014b), and a better scaling with temperature (Ban et al 2014). Further, the convection-permitting approach improves the simulation of the diurnal cycle of summer precipitation (Hohenegger et al 2008;Prein et al 2013). Tölle et al (2014) demonstrated that the influence of land use/cover change is more pronounced when considering the convection-permitting scale, suggesting that local effects of land management are more important than previously thought.…”
Section: Introductionmentioning
confidence: 87%
“…However, at such resolutions, deep convection is parameterized and leads to an overestimation of the net heat transport, rainfall rates, and the net strength of deep convection systems (Prein et al 2013). As a result, such resolutions are still too coarse to capture climate variability at sub-grid scales.…”
Section: Introductionmentioning
confidence: 99%
“…Brockhaus et al 2008;Baldauf et al 2011;Fosser et al 2015). Reaching convection-permitting resolutions allows not only to eliminate a major source of uncertainties and errors, but also to improve the representation of hourly precipitation intensity and spatial distribution (Prein et al 2013;Fosser et al 2015) as well as the representation of surface fluxes (Tölle et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Katragkou et al (2015), Kotlarski et al (2014) and Prein et al (2016). The model configurations for the convection-permitting (3 km grid spacing) simulations in the GAR 15 are based on experiences from previous sensitivity experiments (Suklitsch et al 2011;Awan et al 2011;Prein et al 2013;Prein et al 2015). Our RCMs differ from their coarser resolved counterparts (EURO-CORDEX) insofar that the parametrization for deep-convection has been turned off in the GAR.…”
Section: Study Area and Observation Data 20mentioning
confidence: 99%
“…Their bandwidths are large and (spatial and temporal) correlation coefficients are poor, when they are compared to highly resolved observation data (e.g. 25 Prein et al, 2013). This makes bias correction techniques indispensable, even if deep convection becomes resolved by RCMs.…”
mentioning
confidence: 99%